2013
DOI: 10.1136/jfprhc-2012-100564
|View full text |Cite
|
Sign up to set email alerts
|

Age-related variation in sexual behaviours among heterosexual men residing in Brazil, Mexico and the USA

Abstract: Objective To compare the prevalence of demographic characteristics and sexual behaviours across age groups and to estimate their significance in predicting sexual risk factors by age cohort. Methods This cohort study examined sexually transmitted infection (STI) prevalence among heterosexual men in Brazil, Mexico and the USA (N=3047). Participants completed a sexual risk factor questionnaire and were tested for chlamydia, gonorrhoea, syphilis and genital herpes. We examined sexual risk in the study populatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
0
1
0
2
Order By: Relevance
“…As in other STI studies, a positivity gradient for STIs was observed with advancing age, with individuals over 40 years of age presenting five times more chance of positivity for any of the infections investigated when compared to those under 30 years of age. This result probably reflects lifetime exposures (35)(36) .…”
Section: CImentioning
confidence: 80%
“…As in other STI studies, a positivity gradient for STIs was observed with advancing age, with individuals over 40 years of age presenting five times more chance of positivity for any of the infections investigated when compared to those under 30 years of age. This result probably reflects lifetime exposures (35)(36) .…”
Section: CImentioning
confidence: 80%
“…É possível aproximar os dados do estudo brasileiro de pesquisa realizada nos Estados Unidos 11 , que mostrou maior incidência do agravo entre homens pretos jovens, na faixa etária de 20 a 29 anos. August et al 12 identificaram que, entre os homens mais jovens (18-30 anos), os brasileiros têm sete vezes mais chances de obter resultado reagente para uma IST (herpes genital, clamídia, gonorreia e/ ou sífilis) quando comparados aos norte-americanos.…”
Section: Discussionunclassified
“…Aproximadamente 16% dos conscritos iniciaram a vida sexual com menos de 14 anos e também registraram maior prevalência de sífilis, em contraponto àqueles com uma iniciação mais tardia. August et al 12 mostraram que, dos 3.047 participantes de seu estudo, a maior parte (43,8%) iniciou a atividade sexual entre 15 e 17 anos. Aqueles cuja iniciação sexual ocorreu aos 14 anos ou antes tiveram duas vezes mais chances de apresentar teste reagente para uma IST.…”
Section: Discussionunclassified